Artemisinin relieves myocardial ischemia-reperfusion injury via modulating miR-29b-3p and hemicentin 1 - Han, Junyu; Zhang, Ziguan; Zhang, Zhonghe; Yang, Shuyu (Frontiers in Pharmacology, 2022)
Objective: To explore the impact of artemisinin (ARS) on myocardial ischemia-reperfusion (I/R) injury and the underlying mechanism. Methods: Myocardial I/R rat model and cell model were used in this study. The cell viability, morphological changes, apoptosis and oxidative stress were evaluated in cardiomyocytes H9c2 cells in vitro by using cell counting kit-8, microscope, flow cytometry and commercial kits. High throughput sequencing is used to identify molecular targets of ARS on myocardial I/R injury, and then the gene-gene interaction network was constructed. MiR-29b-3p, hemicentin 1 (HMCN1) and apoptosis-related genes were tested by qRT-PCR and Western blotting. In the myocardial I/R rat model, echocardiography, (Triphenyl tetrazolium chloride) TTC staining, Hematoxylin-eosin (H&E) staining, Masson Trichrome staining and TUNEL staining are applied to evaluate the protective effect of ARS on the myocardial injury. Results: In vitro, we demonstrated that ARS alleviated H2O2-induced myocardial I/R injury, manifested by increased H9c2 viability, decreased pathological changes, apoptosis and oxidative stress biomarker ROS, LDH and CK-MB. Then, sequencing analysis revealed that miR-29b-3p/HMCN1 was the target of ARS for myocardial I/R injury. Notably, rescue experiments indicated that ARS inhibited myocardial I/R injury through targeted regulation miR-29b-3p/HMCN1. In vivo, we confirmed that ARS reduced myocardial injury, fibrosis, and apoptosis via modulation of miR-29b-3p/HMCN1. Conclusion: This study demonstrated the functional role of the ARS/miR-29b-3p/HMCN1 axis in alleviating myocardial I/R injury, which provided a new direction for myocardial I/R injury therapy.